ANOREXIA NERVOSA IN A PAKISTANI ADOLESCENT GIRL: A CASE REPORT - Asghar, Shereen; Alam Khan, Shehzad (Journal of Postgraduate Medical Institute, 2022)
Anorexia nervosa is an eating disorder characterized by very low body weight, excessive self-restriction of food intake due to fear of gaining weight, and a distorted self-perception of the body. We report a case of a 14-year-old girl, admitted to the psychiatry ward with the chief complaints of reluctance to eat and drink, headache, weakness, weight loss, and decreased sleep, for the last year. After the assessment by the psychiatrist, and relevant investigations, she was diagnosed with a case of anorexia nervosa. She was advised to have standard electronic cognitive behavioural therapy, in addition to the pharmacological treatment, and was referred to a dietician who suggested a well-balanced and tailored diet with optimum proportions of macro and micronutrients. After 2 weeks of the initiation of the treatment, her eating habits and negative thoughts were improved and she was discharged from the hospital with a suggested regular follow-up of 2 weeks.